Has anything changed for Fibromyalgia? Focus groups with patients on their lived experiences in England - Cosima Locher; Anna Kharko; Joseph W. Lanario; Leo Druart; Kirralise Hansford; Helen Koechlin; Anthony Davies (PLoS ONE, 2026)
Background While awareness of Fibromyalgia (FM) has evolved across healthcare and social settings, individuals with FM continue reporting poor understanding of their condition in the everyday. Objective To explore the lived experiences and subjective illness narratives of individuals with FM, focusing on personal understandings of FM, outlook on healthcare, and perceived attitudes of surrounding peers. Methods We carried out four online focus groups with individuals diagnosed with FM. Participants were recruited from a pool of patients in a pain management centre in the Southwest of England, UK, that previously took part in a FM management course, ‘Body Reprogramming Course’ (BRC). Discussion topics included the personal understanding of FM (illness identity, timeline, causes, consequences, and controllability), history with FM diagnosis and treatment, attitudes of family and friends towards FM, as well as personal attitude towards medication. Audio recordings from focus groups were transcribed and analysed by two primary coders, using a reflexive thematic analysis approach. Codes were iteratively discussed and refined with two additional coders. Results 20 individuals with FM took part in four focus groups, aged between 25 and 67 years. Analysis of the data revealed 5 overarching themes and 10-subthemes related to lived experiences of FM: 1) The individual journey; 2) FM in healthcare; 3) FM in social context; 4) FM in personal context; 5) Experiences with BRC. Although participants felt that there has been some positive societal shift towards FM, most discussions concerned personal struggles with conveying to family and healthcare professionals the impact of the condition. Participants described a significant emotional toll of dealing with hidden struggles. Many expressed disappointment with prior care, describing it as fragmented, and some expressed strong opposition to medication-based treatments. Reflecting on the BRC, participants liked the coping strategies and the developed connections. Conclusions While participants recognised some positive changes in others’ understanding of FM, the overwhelming sentiment was that FM remains overall poorly received and supported by peers and healthcare professionals. Participants in the BRC described their experience of FM as part of a journey toward a higher purpose, linking their illness to personal growth.